Use of Torrymeter for measurement of freshness of some commercially important Indian marine fishes - Ravi Shankar, C N; Setty, T M R; Shetty, T S (Indian Journal of Fisheries, 2011)
The freshness of mackerel (Rastrelliger kanagurta), oil sardine {Sardinella longiceps), commonshark (Scoliodon laticadus), croaker (Johnius sp.). lizard fish (Saurida tumbil) and seer fish(Scomberomorws commerson), iced immediately after catch, was assesed by using Torrymeier as wellas by other biochemical and microbiological tests and compared with sensory scores obtained. TheTorrymeter readings generally showed good correlation with sensory scores for all the species studiedexcept shark. The decrease of Torrymeter readings was fairly consistant and gradual only in initialstorage period, indicating the usefulness of Torrymeter in measuring the initial loss of freshness of icestoredfish. It was observed that fat content of fish in some way interferes with the reading of theinstrument.